Analisis Waste Pada Proses Produksi Sosis Ayam Dengan Pendekatan Lean Manufacturing Di PT. BI - Giari Ayunintya Pratiwi; Asep Erik Nugraha (Fakultas Teknik Universitas Tulang Bawang, 2023)
PT BI is a food manufacturing company that produces several processed chicken products, one of which is chicken sausage. In the chicken sausage production process, some of waste was found, so a way is needed to improve productivity with the Lean Manufacturing approach, the Value Stream Mapping method. The purpose of this research is to identify waste and provide suggestions for improvements to the chicken sausage production process. From this research, it was identified that five workstations waste, in the Screening area, Preparation, Mixing & Stuffing, Link Cutting, and Multipack Packing. From the results and proposed improvements, it was found that the difference in processing time between the current time and the proposed time was 2.18 hours also the difference in the proposed process line efficiency was 1.72% greater than the current line efficiency. Keywords: Lean Manufacturing, Value Stream Mapping, Waste.